Mit Customer Experience Management die Digitalisierung meistern: Die Rolle von Unternehmenskultur und -organisation - Stephan Bingemer; Martin Ohlwein (Books on Demand (BoD), 2020)
– Confronted with digitization, many companies establish customer experience management (CEM) as a measure to become a customer-centric organization. Based on a pre-study of 25 qualitative interviews with executives from different industries, this paper derives a conceptual approach that helps managers to effectively drive the necessary changes that come along with digitization. This work suggests that digitization is much more a matter of culture and adoption than it is one of technological capabilities and IT invest. This paper provides a segmentation and guides managers confronted with the task to lead their companies towards the "holy grail of digitization".
urn:nbn:de:101:1-2021021900121484890990
Keywords: 650; Beziehungsmarketing; Digitalisierung; Unternehmenskultur